Develop and validate a mathematical model to estimate the removal of indoor VOCs by carbon filters. (1st April 2023) - Khararoodi, Mohamad G.; Haghighat, Fariborz; Lee, Chang-Soo
Abstract: Adsorption-based air filters, especially carbon-based ones, are usually employed to remove VOCs from indoor air. Conducting tests at ppm level, which is substantially higher than the actual indoor concentration of VOCs, is recommended for reducing the test duration. Consequently, developing a model for estimating the service life of adsorptive filters under actual conditions is imperative. A comprehensive model that considers axially dispersed plug flow for interpellet mass transfer and pore surface diffusion model (PSDM) with variable surface diffusivity for intrapellet mass transfer was used to predict the performance of two filters exposed to three VOCs. First, the results of experiments conducted at concentrations ranging from 9 to 90 ppm in a bench-scale setup were used to compute the Dubinin-Radushkevich (D-R) isotherm parameters, which are concentration-independent. Then, the surface diffusivities at zero loading for various adsorbate-adsorbent systems were determined by fitting the developed model into the results of the experimental data performed at concentrations of 9 ppm or 30 ppm. Finally, the model was validated using experimental data which were conducted at lower concentrations, a higher velocity and on a full-scale setup. The inter-model comparison was carried out by comparing the comprehensive model with four other models to study the importance of various mass transfer steps. Finally, in sensitivity analysis, five dimensionless parameters ( Pe, St, E d p, E d s and D g ) were examined to investigate their impact on the filter's efficiency. Highlights: A mathematical model was developed to estimate VOCs removal through carbon filters. The model validation was performed using experimental data and inter-model comparison. Surface diffusion was the predominant internal mass transfer step. The effect of non-dimensional numbers on the system performance was investigated.